Bajo Calima: riqueza biológica y cultural afectada por la extracción de maderas tropicales (2011)
The jungle or the tropical humid forest is a fundamentally biological concept that expresses biodiversity and, therefore, wealth that in this century is easily reduced to units of change such as, for instance, the money. More than half of the wood consumed in Colombia was extracted from the Pacific Coast. Currently the wealth for the Afro-descendant groups of the Bajo Calima is its culture and traditional forms of production, because from the biodiversity and the economic value derived from it, it is quite a lot what they have been subtracted. The article analyzes the participation and distribution of the economic and natural wealth from biodiversity has not brought development for the region.